Optimization of process parameters on friction stir welding of 2014 aluminum alloy plates - Jaiganesh, V.; Srinivasan, D.; Sevvel, P. (International Journal of Engineering and Technology, 2017)
Aluminum Alloy 2014 is a light weight high strength alloy used widely in the aerospace and also in other industries. 2014 is the second most popular of the 2000-series aluminium alloys, after 2024 aluminium alloy. However, it is difficult to weld, as it is subject to cracking. Joining of 2014 aluminium alloy in friction stir welding which is based on frictional heat generated through contact between a rotating tool and the work piece. Determination of the welding parameters such as spindle speed, transverse feed , tilt angle plays an important role in weld strength. The whole optimization process is carried out using Taguchi technique. The SEM analysis is done to check the micro structure of the material after welding by electron interaction with the atoms in the sample. Tensile test have been conducted and the s-n ratio curve is generated. The test is conducted and analysed on the basis of ASTM standards.